Bisnis Halal, Rezeki Berkah: Etika Wirausaha Muslim dalam Arus Kapitalisme - Maulia Dwi Yanti; Fifi Nur Aisha; Lughna Vika Sundusy (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study discusses the ethics of Muslim entrepreneurship in facing the challenges of modern capitalism. Capitalism, characterized by profit orientation, individualism, and materialism, often clashes with the moral and spiritual principles of Islam. Muslim entrepreneurs are expected to uphold the values of honesty, trustworthiness, justice, and excellence (ihsan) in their business practices, even under pressure from efficiency demands and free-market competition. This research uses a qualitative approach with a library research method to explore practical strategies that Muslim entrepreneurs can apply to remain ethical and compliant with Islamic law. The findings show that Islamic ethical principles serve not only as moral guidance but also as a competitive strength in capitalist economic systems.